Prenatal Diagnosis of Two Common Inborn Errors of Metabolism by Genetic and Mass Spectrometric Analysis of Amniotic Fluid - Shi, Congcong; Li, Sitao; Gao, Yu; Deng, Zhirong; Hao, Hu; Xiao, Xin (Frontiers in Pediatrics, 2022)
Methylmalonic acidaemia (MMA) and ornithine transcarbamylase deficiency (OTCD) are both intoxication-type inborn errors of metabolism (IEM). Presently, genetic testing is the primary method for prenatally diagnosing these diseases. However, some reports have demonstrated that mass spectrometry approaches can prenatally diagnose some forms of inborn errors of metabolism using amniotic fluid. Therefore, in this study, genetic and mass spectrometry approaches were used for prenatally diagnosing MMA and OTCD. We collected amniotic fluid samples from 19 foetuses referred, 15 cases were referred for MMA and 4 for OTCD. Of the 15 MMA cases, seven were affected, as determined by genetic testing and the metabolite levels; the characteristic metabolites propionylcarnitine (C3), C3/acetylcarnitine (C2) ratio, methylmalonic acid and methylcitrate levels were significantly higher than the reference range. Eight foetuses were unaffected, and the C3, C3/C2 ratio, methylmalonic acid and methylcitrate levels were within the reference range. The C3, C3/C2, methylmalonic acid, and methylcitrate levels in the amniotic fluid significantly differed between the affected and unaffected foetuses (P=0.0014, P=0.0014, P=0.0003, P=0.0014, respectively). Moreover, the homocysteine level increased in the amniotic fluid of affected foetuses with MMACHC gene mutations. Of the four OTCD cases, genetic testing confirmed that two foetuses were affected and two were unaffected. However, the characteristic metabolite levels were within the reference range for all foetuses, including citrulline, orotic acid, and uracil. The genetic testing results were confirmed to be correct through the abortion tissue of the foetus and the postnatal follow-up. Our results suggest that mass spectrometry approaches are convenient method for improving the prenatal diagnosis of MMA. The characteristic metabolites C3, C3/C2, methylmalonic acid, and methylcitrate levels in amniotic fluid were reliable biochemical markers for the prenatal diagnosis of MMA.